Combined training in addition to cortisol reduction can improve the mental health of girls with precocious puberty and obesity - Heidarianpour, Ali; Shokri, Elnaz; Sadeghian, Efat; Cheraghi, Fatemeh; Razavi, Zahra (Frontiers in Pediatrics, 2023)
Background: Obesity and central precocious puberty (CPP) are associated with increased anxiety, depression, and anger in girls. The contribution of exercise as an efficacious component of a decrease in anxiety, depression, and anger has been increasingly recognized. Objectives: to evaluate the effects of combined training on cortisol, anxiety, depression, and anger in overweight and obese girls with CPP. Methods: The study involved 30 girls aged 7 to 9 who were diagnosed with CPP (undergoing Triptorelin treatment) and were also dealing with obesity. Additionally, these girls scored higher than the cut-off line of anxiety, depression, and anger. The participants were divided into two groups, with 15 individuals in each group. The exercise group engaged in 60 minutes of combined aerobic and 2 This is a provisional file, not the final typeset article resistance training three times per week for a duration of 12 weeks. On the other hand, the control group did not receive any training. Throughout the study, serum cortisol levels were measured in both groups. Anxiety, anger and depression questionnaires were also completed at three different stages: baseline, 12 weeks, and 16 weeks (after a 4-week period of detraining). Results: During the exercise group, there was a significant decrease (P < 0.05) in cortisol serum levels, anxiety, depression, and anger scores. These changes were observed consistently during the detraining period (P>0.05). However, in the control group, only the depression score showed a significant decrease (P < 0.05). Conclusions: Based on the results, it can be concluded that combined training is a method to improve the mental health of CPP girls.